2018
DOI: 10.1007/s13365-018-0636-2
|View full text |Cite
|
Sign up to set email alerts
|

The immune response to picornavirus infection and the effect of immune manipulation on acute seizures

Abstract: Viral infection of the central nervous system can result in encephalitis. About 20% of individuals who develop viral encephalitis go on to develop epilepsy. We have established an experimental model where virus infection of mice with Theiler's murine encephalomyelitis virus (TMEV) leads to acute seizures, followed by a latent period (no seizures/epileptogenesis phase) and then spontaneous recurrent seizures-epilepsy. Infiltrating macrophages (CD11bCD45) present in the brain at day 3 post-infection are an impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 46 publications
3
35
0
Order By: Relevance
“…This agrees with recent work by others investigating the role of microglia in CNS infection with TMEV (Waltl et al 2018b) and with the JHM strain of mouse hepatitis virus (JHMV), another neurotropic virus (Wheeler et al 2018). However, depletion of peripheral macrophages with clodronate-containing liposomes does not result in fatal encephalitis, but instead improves seizure outcomes (DePaula-Silva et al 2018;Waltl et al 2018a). In contrast, microglia-depleted mice maintain the development of seizures and go on to develop paralysis.…”
Section: Discussionsupporting
confidence: 91%
“…This agrees with recent work by others investigating the role of microglia in CNS infection with TMEV (Waltl et al 2018b) and with the JHM strain of mouse hepatitis virus (JHMV), another neurotropic virus (Wheeler et al 2018). However, depletion of peripheral macrophages with clodronate-containing liposomes does not result in fatal encephalitis, but instead improves seizure outcomes (DePaula-Silva et al 2018;Waltl et al 2018a). In contrast, microglia-depleted mice maintain the development of seizures and go on to develop paralysis.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, genetic deletion of either CD4 + or CD8 + cells from B6 mice resulted in viral persistence and demyelination during the chronic stage of disease (Murray et al, 1998). Interestingly, neither CD4 + nor CD8 + cells are required for development of acute seizures following infection with TMEV in B6 mice (DePaula-Silva et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As components of the innate immune response, microglia and macrophages are frequently associated with CNS pathologies such as neuroinflammation. The presence of reactive microglia and infiltration of macrophages into the CNS are often observed during brain inflammation (encephalitis), Parkinson's disease, multiple sclerosis, traumatic brain injury, and brain tumorigenesis, among others [15,[20][21][22][23][24][25]. Upon activation, macrophages can acquire distinct phenotypes such as the classically defined M1, or proinflammatory, and M2, or anti-inflammatory, polarization states.…”
Section: Introductionmentioning
confidence: 99%
“…These acute seizures are characterized by CNS infiltration of immune cells such as macrophages and lymphocytes [15,[34][35][36]. We have previously determined that macrophage infiltration, more specifically IL-6-producing macrophages [15,22,35,36], but not T cell or neutrophil infiltration, is important for seizure development [22]. Recently, we and others have also demonstrated that macrophages and microglia have unique roles in controlling viral infection in the brain [37][38][39].…”
Section: Introductionmentioning
confidence: 99%